Effects of supplemental feeding of Chinese herbal mixtures to perinatal sows on reproductive performance, immunity, and breast milk quality of sows - Duan, Xuelei; Wang, Xiao; Li, Zhaonian; Liu, Chenggong; Zhang, Lu; Bao, Yongzhan; Shi, Wanyu; Zhao, Xinghua (Frontiers in Veterinary Science, 2024)
The aim of this study was to investigate the impact of supplementary feeding with Chinese herbal mixtures on perinatal sows, focusing on their reproductive performance, immunity and breast milk quality. Sixty healthy pregnant sows (Large white, 4 parities) were randomly allocated into five treatment groups (n = 12 per group): the control group received a basal diet, the TRT1 group received a basal diet supplemented with 2 kg/t Bazhen powder (BZP), while the TRT2, TRT3, and TRT4 groups received a basal diet supplemented with 1 kg/t, 2 kg/t, and 3 kg/t Qi-Zhu-Gui-Shao soothing liver and replenishing blood powder (QZGSP), respectively. The trial lasted for a duration of 5 weeks, commencing from day 100 of gestation and concluding on day 21 postpartum. The results showed that supplemental feeding of 2 kg/t and 3 kg/t QZGSP to periparturient sows significantly improved reproductive performance to different degrees, as evidenced by the shortened farrowing intervals and increased average daily feed intake and milk yield. Supplemental feeding of 2 kg/t and/or 3 kg/t QZGSP significantly elevated levels of IL-4, IL-10, IgG, and IgA in sow serum while reduced levels of TNF-α and IL-1β in sow serum. In addition, supplemental feeding of 2 kg/t and 3 kg/t QZGSP to perinatal sows significantly increased the protein and fat content in colostrum and milk. Analysis of 16S rRNA gene amplicon sequencing data in colostrum and milk microbiota revealed that supplemental feeding of QZGSP to perinatal sows is influenced the composition of colostrum and milk composition in sows. Specifically, at the genus level, a decrease in the relative abundance of Escherichia-Shigella, Staphylococcus and Streptococcus was observed in the TRT3 and/or TRT4 groups on day 0 of lactation. The findings from this study indicate that supplemental feeding of 2 kg/t and 3 kg/t QZGSP significantly improved the reproductive performance, immunity and milk quality in sows. Therefore, QZGSP is a beneficial feed additive for perinatal sows.